2003
DOI: 10.1038/nm843
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hepatitis B virus–positive metastatic hepatocellular carcinomas using gene expression profiling and supervised machine learning

Abstract: Hepatocellular carcinoma (HCC) is one of the most common and aggressive human malignancies. Its high mortality rate is mainly a result of intra-hepatic metastases. We analyzed the expression profiles of HCC samples without or with intra-hepatic metastases. Using a supervised machine-learning algorithm, we generated for the first time a molecular signature that can classify metastatic HCC patients and identified genes that were relevant to metastasis and patient survival. We found that the gene expression signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
689
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 792 publications
(731 citation statements)
references
References 35 publications
37
689
2
3
Order By: Relevance
“…As expected, prediction models based on gene expression profiles successfully discriminate HCC from non-tumor livers with expected high accuracy (Kim et al, 2004;Neo et al, 2004;Nam et al, 2005). Many studies have identified differentially expressed gene sets in HCC that differ according to etiological factors (Okabe et al, 2001), mutations of tumor suppressor genes (Chen et al, 2002), rate of recurrence (Iizuka et al, 2003), intrahepatic metastasis (Ye et al, 2003) and different stages (Nam et al, 2005). The results from these studies demonstrate that genomic-scale gene expression profiles recapitulate the well-known morphological distinctions of the tissues and suggest that the differences in gene expression patterns might be biologically relevant.…”
Section: Gene Expression Profiling Of Hccmentioning
confidence: 54%
“…As expected, prediction models based on gene expression profiles successfully discriminate HCC from non-tumor livers with expected high accuracy (Kim et al, 2004;Neo et al, 2004;Nam et al, 2005). Many studies have identified differentially expressed gene sets in HCC that differ according to etiological factors (Okabe et al, 2001), mutations of tumor suppressor genes (Chen et al, 2002), rate of recurrence (Iizuka et al, 2003), intrahepatic metastasis (Ye et al, 2003) and different stages (Nam et al, 2005). The results from these studies demonstrate that genomic-scale gene expression profiles recapitulate the well-known morphological distinctions of the tissues and suggest that the differences in gene expression patterns might be biologically relevant.…”
Section: Gene Expression Profiling Of Hccmentioning
confidence: 54%
“…All data are expressed as means ± SEM. To test the significance of numbers and frequencies of genes or Cy5:Cy3 ratios, we used supervised analyses with the permutation-based method (BRB-ArrayTools, http://linus.nci.nih.gov/ BRB-ArrayTools.html) [16]. This software for the statistical analysis of cDNA microarray gene expression data was developed by the Biometric Research Branch of the National Cancer Institute (USA).…”
Section: Methodsmentioning
confidence: 99%
“…For example, genomic and gene expression analyses have identified key dysregulated signal transduction pathways involved in liver carcinogenesis (Thorgeirsson and Grisham, 2002;Ye et al, 2003;Budhu et al, 2006;Lee and Thorgeirsson, 2006). These studies and others have generated a new paradigm of metastasis ( Figure 3) that is not mutually exclusive to the hypothesis of multistage carcinogenesis depicted in Figure 2.…”
Section: Incidence and Etiology Of Hepatocellular Carcinomamentioning
confidence: 99%